Assessment of Haemostasis in Disseminated Intravascular Coagulation by Use of Point-of-Care Assays and Routine Coagulation Tests, in Critically Ill Patients; A Prospective Observational Study - Kander, Thomas (PLoS One, 2016)
BACKGROUND: Disseminated intravascular coagulopathy (DIC) relates to the consumption of coagulation factors and platelets with bleeding and micro thrombosis events. AIM: The aim of this study was to compare haemostasis parameters in critically ill patients with DIC versus patients without DIC, and in survivors versus non-survivors over time. Correlations between the DIC-score, the degree of organ failure and the haemostasis were assessed. METHOD: Patients admitted to the intensive care unit with a condition known to be associated with DIC and with an expected length of stay of >3 days were included. Routine laboratory tests, prothrombin time, activated partial thromboplastin time, platelet count, fibrinogen concentration and D-dimer were measured. Coagulation and platelet function were assessed with two point-of-care devices; Multiplate and ROTEM. DIC scores were calculated according to the International Society on Thrombosis and Haemostasis and Japanese Association for Acute Medicine. RESULTS: Blood was sampled on days 0–1, 2–3 and 4–10 from 136 patients with mixed diagnoses during 290 sampling events. The point-of-care assays indicated a hypocoagulative response (decreased platelet aggregation and reduced clot strength) in patients with DIC and, over time, in non-survivors compared to survivors. Patients with DIC as well as non-survivors had decreased fibrinolysis as shown by ROTEM. DIC scores were higher in non-survivors than in survivors. CONCLUSIONS: Patients with DIC displayed signs of a hypocoagulative response and impaired fibrinolysis, which was also evident over time in non-survivors. Patients with DIC had a higher mortality rate than non-DIC patients, and DIC scores were higher in non-survivors than in survivors.